Hubungan Konsep Diri Dengan Sikap Percaya Diri Anak Usia 5-6 Tahun Di Tk Negeri 1 Rimba Melintang Kecamatan Rimba Melintang Kabupaten Rokan Hilir - Rahmi Rahmadani; Daviq Chairilsyah; Enda Puspita Sari (Journal on Education, 2023)
The pupose of this study was to determine the relations between self-concept and the self-confidence og children aged 5-5 years at TK Negeri 1 Rimba Melintang, Rimba Melintang District,Rokan Hilir Regency. The type of research used is correlation research. Population and research sample is 30 children. The steps taken in this correlation research are: identifying potentialsand problems, gathering information, determining data collection methods, collection, data analysis, and concluding data. Data collection technique in this study is by using observation sheets. The result of the study show that self-concept and self-confidence among young children have a positive relationship between sel-concept and self-confidence in children aged 5-6 years at TK Negeri 1 Rimba Melintang, Rimba Melintang District, Rokan Hilir Regency. Meaning that if a child has a high self-cocncept then it is followed by a high self-confidence as well, or vice versa. The result of the study show that the coefficient of determination is 54,9%, so it can be seen that self-concept contributes 54,9% to children’s self-confidence.